Effect of childhood pneumococcal vaccination and beta-lactam antibiotic use on the incidence of invasive pneumococcal disease in the adult population - Fernández Chávez, Abelardo; García Comas, Luis; Sanz Moreno, Juan Carlos; Canton Moreno, Rafael; Corral, Octavio Jorge; Aranaz Andrés, Jesús María (European journal of clinical microbiology&infectious diseases, 2021)
Describe the incidence of invasive pneumococcal disease (IPD) in serotypes with reduced antibiotic sensitivity to penicillin (RAS-Pen) in adults over 59 years of age and its association with childhood anti-pneumococcal vaccination coverage (CVC) and community consumption of beta-lactam. We selected IPD cases in adults over 59 years of age reported in the Community of Madrid between 2007 and 2016. We estimated the incidence of cases caused by serotypes included in the 13-valent pneumococcal conjugate vaccine (PCV13), those not included (non-PCV13) and the six serotypes additional to the 7-valent (PCV13-no7). We compared the incidences of serotypes from the pre-vaccine period (2007-2009) and the vaccine period (2011-2016) by analysing the incidence trend (JointPoint Trend Analysis) and its association with the CVC and community consumption of beta-lactam (Poisson model). We identified 1936 cases of IPD, 29.2% (n = 565) in serotypes with RAS-Pen. The incidence decreased for PCV13 cases (annual percentage of change, APC: -12.2, p < 0.05) and increased for non-PCV13 (APC: 15.4, p < 0.05). The incidence of IPD due to non-PCV13 was associated with community beta-lactam consumption (IRR 1.156; CI95% 1.025-1.304) and that of cases of PCV13-no7 with CVC (IRR 0.574; 95% CI95% 0.413-0.797). The non-PCV13 strains that increased the most at the end of the period were 6C, 11A and 15A. The incidence of IPD due to PCV13 with RAS-Pen at > 59 years was decreasing and was associated with CVC. The incidence of cases due to non-PCV13 was increasing and was associated with community consumption of beta-lactam.
Keywords: invasive pneumococcal disease; pneumococcal conjugate vaccine; reduced antibiotic sensitivity; beta-lactam antibiotic; WOS(2); Scopus